45.1k views
4 votes
error analysis correct the error in the following equation explain the mistake 5x + 5(-2x - 12) = 130 5x + -10x - 60 = 130 =65x = 130 x = -2

User Haxwithaxe
by
4.1k points

1 Answer

1 vote

Answer:

Explanation:

The given error full solution is

5x+5(-2x-12)=130

5x+-10x-60=130

65x=130x=-2.

Correct answer is given as

5x+5(-2x-12)=130.

We solve this question using Bodmas rule. So first we remove the parenthesis.

5x+5(-2x-12)=130

5x+5(-2x)+5(-12)=130

5x-10x-60=130

-5x=130+60

-5x=190

dividing both side by by (-5). We, get

x=190/(-5)

x=-38

Hence, the correct answer is x=-5

User Vpap
by
4.2k points